Microbial diagenesis of dissolved organic matter from the ocean’s surface to abyssal depths: a case study in the Humboldt upwelling system - Engel, Anja; Pontiller, Benjamin; Becker, Kevin W.; Amano, Chie; Zhao, Zihao; Herndl, Gerhard J.; Lee, Cindy (Frontiers in Microbiology, 2025)
Marine dissolved organic matter (DOM) represents one of Earth’s largest dynamic carbon pools—comparable in scale to atmospheric CO₂. Primarily derived from phytoplankton production in the sunlit surface ocean, DOM serves as a key substrate for heterotrophic microbes that actively transform and recycle it. The portion remaining after microbial diagenesis contributes to the long-lived deep-sea reservoir of refractory dissolved organic carbon (RDOC) with turnover times up to millennia. DOC lability is an important trait determining microbial utilization as well as carbon storage time in the ocean and can be inferred from its chemical composition, particularly changes in individual amino acids (AAs). In this study, we examined dissolved (DOC) and particulate organic carbon (POC) distribution, composition and concentration of dissolved hydrolyzable AAs (DHAA), microbial community structure, and activity along depth profiles from the surface to the abyssopelagic zone (down to 5,000 m) in the Humboldt upwelling system off Chile—one of the ocean’s most productive regions. Our results show a pronounced decrease in DOC concentration and lability, and in viral and prokaryotic abundance with depth. Below the mesopelagic zone, DOC displayed characteristics of RDOC: <42 μmol C L−1, [DHAA-C]:[DOC] ~ 0.6%, and a glycine fraction of ~75 mol% DHAA. Bacterial biomass production and extracellular enzyme activities (EEA), however, were detectable below the mesopelagic zone and even at abyssal depths, albeit at very low rates. Cell-specific EEA and the proportion of high nucleic acid (HNA) cells increased with depth suggesting adaptation to an extremely low-substrate environment. We discuss microbial carbon turnover under varying assumptions of bacterial growth efficiency and conclude that microbial life in the bathy- and abyssopelagic zones of the Humboldt Current is likely sustained by the flux of sinking particulate organic matter.